The Use of Blended Learning and Its Impact on Developing Graduate Students’ Attitudes at King Abdulaziz University Toward Self-Directed Learning - Al-Sulami, Nada Murizaq (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to investigate the impact of blended learning on developing graduate students’ attitudes toward self-directed learning. The study population consisted of all graduate students in the Faculty of Education at King Abdulaziz University. A purposive sample of (15) female students was selected. Blended learning was applied to all participants using a quasi-experimental design with a one-group pretest–posttest structure to measure its effect on their attitudes toward self-directed learning. A self-directed learning attitude scale was used after confirming its validity and reliability, and additional tools were employed to support the measurement process. Data were analyzed using appropriate statistical methods through the Statistical Package for the Social Sciences (SPSS). The Wilcoxon signed-rank test was used to measure differences between the pre- and post-tests, in addition to calculating the effect size. The results revealed a strong positive effect of blended learning on enhancing students’ attitudes toward self-directed learning, with an effect size of (0.75), indicating its effectiveness in achieving this goal. Based on these findings, the study recommended expanding the use of blended learning in graduate programs and promoting students’ self-directed learning skills.
Keywords: Blended Learning; Self-Directed Learning; Learning Attitudes; Graduate Female Students